UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI MEDIA AUDIO VISUAL SISWA KELAS IV SD NEGERI 04 KLEGEN KOTA MADIUN - Reny Puji Pangestu; Purwandari; Setyaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem that arises in the process of teaching and learning activities is the low level of student absorption in understanding the material presented by the teacher and student learning outcomes. The factor that really influences it is the use of learning media which has not been implemented optimally so that students are bored with the learning media which is still monotonously used by teachers in the learning process. Judging from its use at SD Negeri 4 Klegen, especially in the Pancasila Education subject in class IV, teachers have not utilized a variety of learning media in the learning process. This research aims to determine the learning outcomes of Pancasila education in class IV of SD Negeri 4 Klegen, Madiun City after using audio-visual media. This research stage begins with action planning, action implementation, observation and reflection. Analysis of the final results shows that the learning outcomes for Pancasila Education on the Meaning of the Unitary State of the Republic of Indonesia before using Audio Visual media were very low. It was proven that only 2 students or 17% completed above the KKM. Student learning outcomes have increased, the results of this research are in the form of increased student learning outcomes in the Pancasila Education subject, material on the meaning of the unitary state of Indonesia. During the pre-test cycle I, the results obtained were that the percentage of student learning completion was (34%) with an average score of (64%) with the number of students who completed 4 people and 8 students who did not complete it or (66%). Meanwhile, in cycle II the average class score reached 82.5% with a completion rate of 83%. The conclusion is that with the implementation of audio visual media students are more enthusiastic and motivated in participating in the learning process compared to before the action was given.